Establishing normal gallbladder volume: a comparative study of dual energy computed tomography and ultrasound measurements in a North Indian population - Khanduri, Sachin; Fatima, Ambreen; Khan, Salma; Khan, Zaara; Sharma, Vasundhara; Dhingra, Vibhor; Bansal, Tanya; Yadav, Akshat Kumar; Ahmad, Mugheer; Husain, Saddam (International Journal of Research in Medical Sciences, 2024)
Background: The gallbladder, a critical component of the biliary system, plays a vital role in bile storage and digestion. Dysfunction in the gallbladder often results in gallstone formation, leading to significant healthcare burdens worldwide. Gallstone disease and gallbladder carcinoma are major health concerns, particularly in regions like India, where prevalence is high and poorly understood. Methods: This study aims to establish the normal baseline volume of the gallbladder using dual-energy computed tomography (DECT) and compare it with measurements obtained via ultrasound (USG). The cross-sectional study conducted at Era’s Lucknow medical college and hospital involved 265 individuals aged 18-80 years with non-gallbladder-related abdominal conditions. Results: Final results showed the mean gallbladder volume to be 29.33±8.70 cm3 by DECT and 27.40±8.58 cm3 by USG, with DECT measurements being on average 1.93 cm3 higher. A significant association was found between gallbladder volume and obesity, but not gender. Conclusions: The findings suggest DECT provides slightly higher and potentially more accurate measurements of gallbladder volume compared to USG. These insights contribute to a better understanding of gallbladder physiology and the implications of its volume in various pathologies, emphasizing the need for further studies with larger sample sizes to validate these observations.